Into the water - Hawkins, Paula (Doubleday, 2017)
In the last days before her death, Nel called her sister. Jules didn't pick up the phone, ignoring her plea for help. Now Nel is dead. They say she jumped. And Jules has been dragged back to the one place she hoped she had escaped for good, to care for the teenage girl her sister left behind. But Jules is afraid. So afraid. Of her long-buried memories, of the old Mill House, of knowing that Nel would never have jumped. And most of all she's afraid of the water, and the place they call the Drowning Pool